Pengaruh Promosi Jabatan Dalam Meningkatkan Kinerja Karyawan Di Departemen Housekeeping Pada Hotel Grandhika Setiabudi Medan - Siringo-ringo, Andre Permadi (Tourism, Hospitality And Culture Insights Journal, 2023)
This study aims to determine promotion at Hotel GranDhika Setiabudi Medan, to determine employee performance at Hotel GranDhika Setiabudi Medan, and to determine the effect of promotion on employee performance at Hotel GranDhika Setiabudi Medan. The research method used is a quantitative method. Data collection techniques in this study are through observation and questionnaires. The population in this study were housekeeping employees at Hotel GranDhika Setiabudi Medan. This study used a sample of 28 respondents. The sample was taken from the GranDhika Hotel housekeeping employees to fill out a questionnaire distributed through an online survey platform. Based on the results of the study, it was found that promotion at Hotel GranDhika Setiabudi Medan has a positive effect on employee performance and the fairer and better the promotion is carried out, the better the employee's performance.[DM1]The effect of promotion on employee performance at Hotel GranDhika Setiabudi Medan is a positive and significant influence where promotion can affect employee performance by 44.3% and the remaining 55.7% is influenced by other factors outside of this study.